Pengaruh office channeling dan dana pihak ketiga terhadap laba dengan pembiayaan sebagai variabel intervening pada Perbankan Syariah di Indonesia - Muhammadinah Mamad (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2020)
This research aims to determine the influence of Office Channeling and third party funds to profit with financing as a variable intervening on sharia banking in Indonesia. The population in this study is the entire sharia banking in Indonesia consisting of 14 Sharia commercial banks and 20 Syariah business units. Then the sample used is the summary (summary) of Sharia banking financial statement period of 3 years on a monthly basis so that the number of samples as much as 12 x 3 = 36. The analytical technique used is Path analysis using Test T, where the mediation test is done with the procedure developed by Sobel (1982) and known as Sobel Test. The results showed that: a) the Office Channeling variable was directly influential and insignificant to the financing variable. b) The variables of the third party fund are directly influential and significant to the financing variable. c) The Office Channeling variable is directly influential and significant to the profit variable. d) Variable third party funds are directly influential and insignificant to the profit variable. e) The financing variable is directly influential and significant to the profit variable. f) The financing variable is not able to view the influence of the Office Channeling variable on profit variable. g) The financing variable is capable of imradiation the influence of third-party funds variables to profit variables.